Electricity transmission, distribution and storage systems - Melhem, Ziad (Woodhead Publishing, 2013)
Advanced electricity transmission and distribution (T & D) network technologies are required to reduce losses, sustain higher network efficiency, and maintain power quality and security. Research in this field must also consider the increasing role and penetration of renewable and distributed generation, for which advanced electricity storage systems are required. The first section of this book presents chapters on key aspects of the materials, architecture and performance of electricity T & D networks. The second section addresses the applications and integration of electricity storage systems.
Keywords: Electric power transmission.; Electric power distribution.; elektronické knihy; electronic books